PENGARUH PEMBERIAN YOGURT SINBIOTIK PISANG TERHADAP KADAR GLUKOSA DARAH PASIEN SINDROM METABOLIK - Adam Ozelan; Suhaema Suhaema; Fifi Luthfiyah; Ni Ketut Sri Sulendri (Poltekkes Kemenkes Mataram, 2021)
Background : The metabolic syndrome (MS) as a collection of risk factors for cardiovascular disease and diabetes. One alternative food intake that can reduce the risk of MS by consuming synbiotics, which is a combination of probiotics with prebiotics. Prebiotics in the form of inulin, Fructooligosaccharide (FOS), and resistant starch cannot be digested in the small intestine so that probiotic bacteria will be fermented in the colon and produce Short Chained Fatty Acid (SCFA), so that hypoglycemic effects can occur. Objectives : To know the effect of giving synbiotic to blood glucose levels on MS. Research Methods : Randomized Controlled Trial (RCT) with a pretest-posttest with control group design in metabolic syndrome patients domiciled in Mataram. A total of 24 subjects were divided into 2 groups: the treatment group by administering sinbiotic yogurt with kepok banana flour was 260 ml / day for 14 days, while the control group was not treated. Results : The Blood paired t test results showed differences in the mean glucose level in the treatment group before and after the intervention was 7.83 ± 21.319 mg / dL (p = 0.229), while the control group was -2.25 ± 18.202 mg / dL (p = 0.677). The difference in the decrease in glucose levels of the two groups is 10,083 ± 8.092 mg / dL (p = 0.226) which shows insignificant differences. Conclusion : There is no effect of sinbiotic yogurt to blood glucose levels in metabolic syndrome patients